Protein S-acyltransferases and acyl protein thioesterases, regulation executors of protein S-acylation in plants - Li, Jincheng; Zhang, Manqi; Zhou, Lijuan (Frontiers in Plant Science, 2022)
Protein S-acylation, also known as palmitoylation, is an important lipid post-translational modification of proteins in eukaryotes. S-acylation plays critical roles in a variety of protein functions involved in plant development and responses to abiotic and biotic stresses. Status of S-acylation on proteins is dynamic and reversible, which is catalyzed by protein S-acyltransferases (PATs) and reversed by acylthioesterases. The cycle of S-acylation and de-S-acylation provides a molecular mechanism for membrane associated proteins undergo cycling and trafficking between different cell compartments and thus works as a switch to initiate or terminate particular signaling transductions on membrane surface. In plants, thousands of proteins have been identified to be S-acylated through proteomics. Many S-acylated proteins and quite a few PAT-substrate pairs have been functional characterized. A recent characterized acylthioesterase family, ABAPT family proteins in Arabidopsis has provided new insights into the de-S-acylation process. However, our understanding of the regulatory mechanisms controlling the S-acylation and de-S-acylation process is surprisingly incomplete. In this review, we discuss how protein S-acylation level is regulated with the focus on the catalyzing enzymes in plants. We also propose the challenges and potential developments for the understanding of the regulatory mechanisms controlling protein S-acylation in plants.